2019
DOI: 10.30880/jtmb.2019.06.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Nurturing Entrepreneurship Ecosystem in a Developing Economy: Myths and Realities

Abstract: Entrepreneurship is considered as a panacea for economic infirmities. Development and prosperity can be fostered, upon the organized availability of the required resources, ambidextrously. Entrepreneurship ecosystem is an appropriate approach where a systematic and conducive atmosphere for business activities is paved by providing support and services in the area of business policy, financing, human capital availability, infrastructure accessibility, entrepreneurial culture orientation and internationalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Big data is a popular Industry 4.0 technology that can manage large quantities of data such as transmission, collection, structured and unstructured data processing for decision-making as well as storage (Vidgen, 2014). Furthermore, it adopts a systematic approach to identifying and explicates knowledge as original thoughts (Mubarak et al , 2019a, b). Consequently, through the introduction of big data analytics, the credibility and reliability of vendors, partners and other stakeholders may be assessed by evaluating their past performance records, company portfolio and partnerships.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Big data is a popular Industry 4.0 technology that can manage large quantities of data such as transmission, collection, structured and unstructured data processing for decision-making as well as storage (Vidgen, 2014). Furthermore, it adopts a systematic approach to identifying and explicates knowledge as original thoughts (Mubarak et al , 2019a, b). Consequently, through the introduction of big data analytics, the credibility and reliability of vendors, partners and other stakeholders may be assessed by evaluating their past performance records, company portfolio and partnerships.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The establishment of an environment that encourages entrepreneurship and facilitates the growth of prosperous incubators ought to be a top priority for policymakers and other relevant parties (Sultana & Gupta, 2023). Policymakers can establish an ecosystem that gives incubators the tools and assistance they need to succeed by concentrating on elements like government backing, networking opportunities, mentorship programs, and funding availability (Krebs et al, 2022;Mubarak et al, 2019). Furthermore, cooperation between different stakeholders-universities, businesses, and incubators, among others-is critical to the growth of a robust entrepreneurial ecosystem (Vrabec et al, 2023).…”
Section: Entrepreneurial Ecosystemmentioning
confidence: 99%
“…Hermanto (2017) studied the EE policy in Indonesia and reported that the Government was in need of a comprehensive plan to coordinate and execute entrepreneurship initiatives and had to establish a ministry for entrepreneurship policy-making. Mubarak et al. (2019) examined the EE in the developing economy of Pakistan, confirmed the “central” role of the Government and proposed that a specific national policy for entrepreneurship be regarded as a top priority.…”
Section: Literature Reviewmentioning
confidence: 99%